The impact of high-technology trade on employment - Idris, Zera Zuryana; Ismail, Normaz Wana; Ibrahim, Saifuzzaman; Hamzah, Hanny Zurina (Routledge, 2021)
This paper aims to empirically examine the impact of high-technology trade on employment. A dynamic labour demand equation is employed to investigate the impact of high-tech trade on employment in 20 high-tech exporting countries. Using data from 2007 to 2016, this study highlights some evidence on the negative relationship between high-tech trade and employment. This paper argues the development towards high-tech trade should be accompanied by appropriate policy measures to lessen the employment effect and to ensure the benefit of growth is well-distributed among all segments of the labour market.